SYTEMATIC LITERAURE REVIEW : PENERAPAN METODE ALGORITMA C4,5 UNTUK KLASIFIKASI - Srifani, Dewi; Nugroho, Bangkit Indarmawan; Santoso, Nugroho Adhi (Jurnal Informatika UPGRIS, 2022)
Abstract---Data mining is extracting data in processing information with the aim of finding important patterns in piles of data. With data mining we can classify, predict, and make a decision. Classification is a way of grouping a data according to the characteristics of a data to be classified. In the process, the classification is divided into two, namely manually and with the help of technology. Manual classification is a classification carried out by humans without the help of technology, while classification with the help of technology has several algorithms, including C4.5, Naive Bayes, Fuzzy, and K-Nearest Neighbor. 5 for classification, a systematic approach is used in the form of a systematic literature review (SLR). SLR is defined as a process in which the identification, assessment, and interpretation of all available research evidence is carried out with the aim of answering a number of research questions